1968
DOI: 10.1113/jphysiol.1968.sp008427
|View full text |Cite
|
Sign up to set email alerts
|

Release of noradrenaline from the cat spleen by potassium

Abstract: SUMMARY1. Cat spleens were perfused with Krebs-bicarbonate solution by means of a constant flow pump. The amount of noradrenaline released by an injection of potassium chloride solution (3.7M) was measured. The dependence of noradrenaline released by KCI on the ionic composition of perfusion medium was determined.2. In normal cats, the average output was 166 ng following a low dose of KCI (0'2 ml.), and 507 ng following a high dose (0.8 ml.). After phenoxybenzamine treatment, the outputs with both doses were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(45 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…Tissues lose their noradrenaline content when exposed to a lowsodium environment (Kirpekar & Wakade, 1968a;Bogdanski & Brodie, 1969;Garcia & Kirpekar, 1973). Experiments carried out to see if bretylium was released from the sympathetic nerve terminals by exposure to sodium-free medium clearly demonstrated that like noradrenaline, bretylium was released leading to an impairment of the ability of the tissue to retain [3H] -noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues lose their noradrenaline content when exposed to a lowsodium environment (Kirpekar & Wakade, 1968a;Bogdanski & Brodie, 1969;Garcia & Kirpekar, 1973). Experiments carried out to see if bretylium was released from the sympathetic nerve terminals by exposure to sodium-free medium clearly demonstrated that like noradrenaline, bretylium was released leading to an impairment of the ability of the tissue to retain [3H] -noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…Ten min after the last washout the control preparation was exposed to bretylium (20;ig/ml for 5 minutes). (Kirpekar & Wakade, 1968a;Bogdanski & Brodie, 1969;Garcia & Kirpekar, 1973 (Figure 5, column B). On the other hand, in the half atrium treated with bretylium in normal Krebs, and then switched to sodium-free (sucrose) Krebs, retention of [ 3 H] -noradrenaline was also markedly decreased ( Figure 5, column C).…”
Section: Effect Of Potassium Deprivation On the Abili7 Of Bretylium mentioning
confidence: 99%
“…In addition, the observation that the evoked release of noradrenaline is potentiated in a sodium-free medium (Kirpekar & Wakade, 1968a) suggests that a competition between sodium and calcium ions may exist at the sympathetic nerve endings to modulate the release of noradrenaline. Competition between these ions has been observed in the contraction of the heart (Luttgau & Niedergerke, 1958) and the release of acetylcholine at cholinergic nerve endings (Birks, Burstyn & Firth, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous release of endogenous noradrenaline in a sodium-deficient medium may be attributed to the failure of the uptake mechanism, since the transport mechanism for the uptake of exogenous catecholamine, and presumably the uptake of endogenous noradrenaline, is mediated by a specific sodium-dependent carrier mechanism (Iversen & Kravitz, 1966;Gillis & Paton, 1967;Kirpekar & Wakade, 1968a) located in the axonal membrane. In addition, the observation that the evoked release of noradrenaline is potentiated in a sodium-free medium (Kirpekar & Wakade, 1968a) suggests that a competition between sodium and calcium ions may exist at the sympathetic nerve endings to modulate the release of noradrenaline.…”
Section: Introductionmentioning
confidence: 99%
“…The net fractional release obtained with 10 mM 4-AP amounted to 22 and 28% in 2.5 and 0 Ca"+, respectively (P = 0.05). (Kirpekar & Misu, 1967;Kirpekar & Wakade, 1968 Effect oftetrodotoxin on tetraethylammonium-induced tritium release…”
Section: Incubation and Perfusion Solutionsmentioning
confidence: 99%